Technologies for digital video products in the next generation of consumer electronics - Yau, Nicholas Yew Suen. (2008)
This project was embarked upon to analyze the latest technologies of consumer electronics field. It is concentrated on studying the technologies of the consumer video products for the next generation — Digital Video Cameras (DVC) and DVD-RAM. This project also keeps an eye on the fast developing trends of the future technology, innovation and perfect consumer digital products.